The Effects of Nitrogen Fertilizer on Soil - Stone, Loyal R.; Whitney, David A.; Janssen, Keith A.; Long, James H. (My University, 1991)
This publication explores the use of nitrogen fertilizer on soil in different plant-available forms.
C625_1991_05
Keywords: C625; Crops; C